(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The process of training highly qualified specialists in physical education is important for the development of modern society. They must have the knowledge and skills necessary to successfully work with students and pupils in their professional work. This approach allows them to successfully apply their professional skills in practice and make a significant contribution to social development. However, today higher education is focused on training specialists who are able to perceive and improve themselves in accordance with changes in society, develop and acquire new knowledge. Thus, increasing the level of quality training of specialists in the field of physical culture and sports is one of the strategic tasks of the educational policy of higher education institutions at the current stage. Psychological-pedagogical training of future physical culture specialists should provide a holistic view of work and motivation for professional activity. The article highlights and analyzes the psychological and pedagogical conditions that are aimed at the quality training of future specialists in physical culture. Scientists define future specialists in physical culture and sports as a person who purposefully acquires qualifications in higher education institutions according to a certain educational and qualification level. At the same time, during professional training at a higher educational institution, such a specialist must form an appropriate level of professional competence, which will be sufficient for successful work in all areas of sports movement, taking into account the demands of society. The future specialist is a person who is in constant search, and his professional activity is aimed at creative and motor components. Physical education is an integral part of the education system, it provides knowledge about health in general, ways to strengthen and strengthen it, achieve a certain physical form, a high level of work capacity and creative activity.